2007
DOI: 10.1371/journal.pone.0000290
|View full text |Cite
|
Sign up to set email alerts
|

Stability of mRNA/DNA and DNA/DNA Duplexes Affects mRNA Transcription

Abstract: Nucleic acids, due to their structural and chemical properties, can form double-stranded secondary structures that assist the transfer of genetic information and can modulate gene expression. However, the nucleotide sequence alone is insufficient in explaining phenomena like intron-exon recognition during RNA processing. This raises the question whether nucleic acids are endowed with other attributes that can contribute to their biological functions. In this work, we present a calculation of thermodynamic stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…It has also been suggested that the thermodynamic stability of DNA/DNA and mRNA/DNA duplexes affects mRNA transcription (24). Here, we analyze the genome-wide data for the calculated thermodynamic stability of DNA/DNA and RNA/DNA duplexes in yeast obtained from published sources (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that the thermodynamic stability of DNA/DNA and mRNA/DNA duplexes affects mRNA transcription (24). Here, we analyze the genome-wide data for the calculated thermodynamic stability of DNA/DNA and RNA/DNA duplexes in yeast obtained from published sources (24).…”
Section: Resultsmentioning
confidence: 99%
“…Intron sequences were downloaded from the Ares lab Intron Database (version 3.0) (http://compbio.soe.ucsc.edu/yeast_introns.html). From literature sources, we obtained data sets for the transcriptome (19–22), protein abundance (23), the average values of ΔG for mRNA/DNA and DNA/DNA duplex stabilities of CDS (window size 9 bp) (24), nucleosome occupancy (25), protein and mRNA high-confidence cellular levels of 408 genes (26) and parallel analysis of RNA structure (PARS) scores (27). …”
Section: Methodsmentioning
confidence: 99%
“…While these ideas are speculative, studies on RNA/DNA hybrid stability support these ideas. In particular, poly-rU/poly-dA hybrids (akin to those occurring just upstream of the TSS) are the least stable, and poly-rA/poly-dT hybrids (akin to the downstream arrangement) are the most stable of all RNA/DNA hybrid tracts consisting of only A or T (or U) (Sugimoto et al 1995;Kraeva et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown [8][9][10] that the 5 0 -and 3 0 -untranslated regions (UTRs), introns and exons have characteristic guanine/cytosine (GC) content, which could affect RNA transcription and processing. Nucleotide composition could influence protein recruitment 9 , RNA secondary structure 10 , transcription rate 11,12 , DNA melting 13 or RNA/DNA and DNA/DNA duplex stability 14 . The free energy (DG) necessary to unwind polynucleotide duplexes with defined length can be calculated from the measured values of entropy (DS) and enthalpy (DH) for the 10 possible nearest-neighbour DNA/ DNA [15][16][17][18][19][20] interactions, and the 16 possible RNA/DNA 21,22 interactions.…”
mentioning
confidence: 99%
“…The free energy (DG) necessary to unwind polynucleotide duplexes with defined length can be calculated from the measured values of entropy (DS) and enthalpy (DH) for the 10 possible nearest-neighbour DNA/ DNA [15][16][17][18][19][20] interactions, and the 16 possible RNA/DNA 21,22 interactions. We have previously shown that exons possess more stable RNA/DNA duplexes than introns in Saccharomyces cerevisiae 14 . However, our original approach did not allow for direct comparisons between the stability of RNA/DNA and DNA/ DNA duplexes because the DS and DH parameters used for DNA/ DNA duplexes 19 lead to overestimation of its DG in comparison with DG of RNA/DNA duplexes.…”
mentioning
confidence: 99%